2019
DOI: 10.1002/lsm.23063
|View full text |Cite
|
Sign up to set email alerts
|

Photobiomodulation with polychromatic light increases zone 4 survival of transverse rectus abdominis musculocutaneous flap

Abstract: Objective The aim of this study was to evaluate the effect of relatively novel approach of application of polychromatic light waves on flap survival of experimental musculocutaneous flap model and to investigate efficacy of this modality as a delay procedure to increase vascularization of zone 4 of transverse rectus abdominis musculocutaneous (TRAM) flap. Methods Twenty‐one Wistar rats were randomized and divided into 3 experimental groups (n = 7 each). In group 1 (control group), after being raised, the TRAM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 40 publications
(42 reference statements)
3
7
0
Order By: Relevance
“…28 Increased neovascularization in experimental skin-muscle flap has been demonstrated by the authors previously. 11 In accordance…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…28 Increased neovascularization in experimental skin-muscle flap has been demonstrated by the authors previously. 11 In accordance…”
Section: Discussionmentioning
confidence: 99%
“…Castro et al found improved integration and viability of the skin grafts in rats when exposed to laser PBM at 660 nm, 40 mW, 60 s, 2.4 J for 7 days 44 . Calis et al reported improved survival of zone 4 skin in transverse rectus abdominis myocutaneous flap model in rats when polychromatic light PBM at 600–1200 nm for 12 min was applied for 7 days in 48 h intervals 11 . However, literature data lacks information about photobiomodulation modalities and their influence on fat grafting procedure.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations